Flooding in the James Bay region of Northern Ontario, Canada: Learning from traditional knowledge of Kashechewan First Nation. (May 2019) - Khalafzai, Muhammad-Arshad K.; McGee, Tara K.; Parlee, Brenda
Abstract: Traditional Knowledge has the potential to increase our understanding of many kinds of ecological phenomenon including floods. This article offers insights into the nature of spring flooding and its impacts in the southwestern James Bay region of northern Ontario, Canada from the perspectives of residents of Kashechewan First Nation. This article highlights the important contribution of Kashechewan First Nation's traditional knowledge to understanding and reducing disaster risks in this flood-prone region. Through a collaboration with Kashechewan First Nation, traditional knowledge was documented in 2016 during 17 in-depth interviews, participatory flood mapping workshops, on-site walks, and photography. The results of this study show that spring flooding has occurred seasonally over many generations in the region and has not increased significantly over time. However, the timing and extent of spring flooding has changed in recent years with warming temperatures in the region (i.e., earlier spring, snowmelt, and rapid runoff) and impacts are exacerbated by landscape and resource developments (e.g., inadequate infrastructure, substandard ring-shaped dyke wall, and downriver winter ice road) which have increased the frequency and scale of spring ice breakup and ice jams. These ecological changes have created the increased risk of flooding for the community of Kashechewan. The methodological approach which used participatory techniques may be useful for ongoing flood monitoring and disaster risk reduction activities in southwestern James Bay and elsewhere among the Canadian Indigenous communities.